D-optimal Design for Preparation and Optimization of Fast Dissolving Bosentan Nanosuspension - Elham Ghasemian; Parisa Motaghian; Alireza Vatanara (Tabriz University of Medical Sciences, 2016)
Purpose: Bosentan is a drug currently taken orally for the treatment of pulmonary arterialhypertension. However, the water solubility of bosentan is very low, resulting in lowbioavailability. The aim of this study was preparation and optimization of bosentannanosuspension to improve solubility and dissolution rate.Methods: The different formulations designed by Design Expert® software.Nanosuspensions were prepared using precipitation method and the effects of stabilizer typeand content and drug content on the particle size, polydispersity (PDI) and yield ofnanosuspensions were investigated.Results: Particle size, PDI and yield of the optimal nanosuspension formulation were 200.9nm, 0.24 and 99.6%, respectively. Scanning electron microscopy (SEM) results showedspherical morphology for bosentan nanoparticles. Thermal analysis indicated that there wasa partial crystalline structure and change in the pholymorphism of bosentan in thenanoparticles. In addition, reduction of particle size, significantly increased in vitrodissolution rate of the drug.Conclusion: Optimization by design expert software was shown to be a successful methodfor optimization and prediction of responses by less than 10% error and formulation with15.8 mg span 85 as an internal stabilizer and 45 mg drug content were introduced as theoptimum formulation. The solubility of bosentan in the optimal formulation was 6.9 timeshigher than coarse bosentan and could be suggested as promising drug delivery systems forimproving the dissolution rate and possibly the pharmacokinetic of bosentan.